Comparison of fracture resistance of endodontically treated mandibular first molars restored with different reinforcing materials with and without cusp capping - Vaishnavi J Singh; Shivkumar P Mantri; Bonny Paul; Kavita A Dube; Nishikumari Gupta; Sayantani Ghosh (Wolters Kluwer Medknow Publications, 2021)
Aim: This study aims to estimate and compare the fracture resistance of endodontically treated mandibular first molar restored with reinforced composite resin or cusp capping. Materials and Methods: Seventy-five freshly extracted intact mandibular molars were randomly divided into five groups. The teeth were embedded vertically into the self-cure acrylic lined with elastomeric impression material to a level 1 mm apical to the cement-enamel junction. Group 1 included intact teeth. After access preparation in Groups 2-5, canals were negotiated with 10 K file, cleaned shaped using K3XF NiTi rotary files, 17% Ethylenediaminetetraacetic acid, and 3% sodium hypochlorite. After drying, the canals were obturated with gutta-percha and Sealapex sealer. Group 2 teeth were restored using Cavit. In Groups 3-5, the access cavity floor was lined by resin-modified glass-ionomer cement. After etching, rinsing, and bonding, teeth were restored. Group 3 teeth with everX posterior as a base and 1.5 mm of occlusal nanohybrid composite. Group 4 teeth were restored with nanohybrid composite after bonding Interlig fiber circumferentially in the access cavity. In Group 5, after 2 mm cusp reduction, etching, and bonding, teeth were restored by cusp capping using nanohybrid composite. All specimens were subjected to a fracture test. The peak-load fracture value in Newton was recorded. Results: One-way analysis of variance test for intergroup comparison revealed a statistically significant difference between the groups (P = 0.011). Post hoc Tukey's test showed a significant difference (P = 0.005) between everX posterior and Cavit specimens. The Chi-square test results revealed that there is a significant difference (P = 0.0276) in the fracture pattern between the groups. Conclusion: It is concluded that restoration using short fiber-reinforced composite improved the fracture resistance of endodontically treated mandibular molars. Cusp-capped teeth exhibited more favorable fractures. The combined use of fiber-reinforced composite and capping the cusps using nanohybrid composite could be a viable option to restore molar favorably.